Dynamic imaging and pathological changes in pig liver after MR-guided microwave ablation - Dong, Jun (BMC Cancer, 2018)
BACKGROUND: Magnetic resonance (MR)-guided microwave ablation is a well-developed technique for the treatment of tumors, especially hepatic carcinomas. However, there are no detailed reports on the changes in the MR images and histology observed after the ablation. This study aimed to dynamically map the pathological changes after ablation and the changes occurring on MR images. METHODS: We performed MR-guided microwave ablation in 10 Wuzhishan pigs and obtained an MR scan immediately after ablation (0 weeks) and at 1, 2, 3, and 4 weeks after ablation. We compared the ablation assessed on MR images to tissue specimens obtained during follow-up. RESULTS: We found no significant difference in the ablation size between MR images and tissue specimens; the mean length and width of the ablated zone were 4.27 cm and 2.42 cm, respectively, on MR images and 4.26 cm and 2.45 cm, respectively, on specimens (P > 0.05). Immediately after ablation, carbonization and cavities were observed in the center of the ablation zone. Surrounding layer cells were necrotic but maintained their original shapes. The outermost layer was inflamed, but gradually showed fibrotic characteristics. The MR images accurately reflected the exact histological tissue changes after the ablation procedure. CONCLUSION: The dynamic imaging and pathological features of liver ablation outlined in this study will provide a useful reference for patient follow-up after MR-guided microwave ablation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4157-4) contains supplementary material, which is available to authorized users.